2008
DOI: 10.1007/s11145-008-9119-9
|View full text |Cite
|
Sign up to set email alerts
|

Code-oriented instruction for kindergarten students at risk for reading difficulties: a replication and comparison of instructional groupings

Abstract: The purposes of this study were to replicate previous research on phonicsbased tutoring in kindergarten and to compare treatment effects for students who received individual instruction compared to instruction in dyads. Thirty classroom teachers from 13 urban elementary schools referred at-risk students for participation. Students who met screening criteria were quasi-randomly assigned, within classroom, to one of three conditions: individual tutoring (n = 22), tutoring in dyads (n = 32), or no tutoring (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…Results from our posttest models (see Table 5) show, first, that treatment effects largely replicate the results of previous kinder- garten studies (Vadasy & Sanders, 2008a, 2008bVadasy et al, 2006a). Holding all other variables constant, treatment students significantly outperformed controls on every posttest except phonological awareness: treatment students averaged 13.54 more letters correct per minute, 7.82 more standard score points on word reading, 24.50 more points on developmental spelling, 13.18 more words correct per minute on passage reading fluency, and 6.00 more standard score points on comprehension (recall that treatment status was effect coded).…”
Section: Research Questions 1 and 2: What Are The Impacts Of Treatmensupporting
confidence: 79%
See 1 more Smart Citation
“…Results from our posttest models (see Table 5) show, first, that treatment effects largely replicate the results of previous kinder- garten studies (Vadasy & Sanders, 2008a, 2008bVadasy et al, 2006a). Holding all other variables constant, treatment students significantly outperformed controls on every posttest except phonological awareness: treatment students averaged 13.54 more letters correct per minute, 7.82 more standard score points on word reading, 24.50 more points on developmental spelling, 13.18 more words correct per minute on passage reading fluency, and 6.00 more standard score points on comprehension (recall that treatment status was effect coded).…”
Section: Research Questions 1 and 2: What Are The Impacts Of Treatmensupporting
confidence: 79%
“…Tutored students also maintained significantly higher levels of growth at follow-up at the end of first grade. The subsequent two studies (Vadasy & Sanders, 2008a, 2008b replicated these results.…”
Section: Research Questionsmentioning
confidence: 68%
“…Our finding of significant positive treatment effects on all but one of our outcome measures (across LM and non-LM students) replicates earlier results on the effectiveness of paraeducator-implemented, supplemental phonics-based instruction for at-risk kindergarteners (Vadasy & Sanders, 2008a;Vadasy, Sanders, & Peyton, 2006a), first graders (Jenkins et al, 2004;Vadasy et al, 1997aVadasy et al, , 1997b, and children in Grades 2 and 3 (Vadasy, Sanders, & Peyton, 2006b; …”
Section: Discussionsupporting
confidence: 88%
“…Although there may be a relation between treatment implementer and the frequency of fidelity reporting, there appears to be a threat to the validity of this finding. Patricia Vadasy was the first author on nine of the 22 studies conducted with paraprofessionals, and all of these studies reported treatment fidelity (Vadasy and Sanders 2008a; Vadasy and Sanders 2008b; Vadasy and Sanders 2010; Vadasy and Sanders 2011; Vadasy et al 2005; Vadasy et al 2006a; Vadasy et al 2006b; Vadasy et al 2007; Vadasy et al 2002, b). If these studies were removed, the percentage of studies with paraprofessional implementers reporting treatment fidelity (46%) would have approximated the level of treatment fidelity reporting across all studies (47%).…”
Section: Resultsmentioning
confidence: 99%